In silico Study of Essential Oil of Bambusa vulgaris Leaves as an Anti Beta-lactamase Compound - Pragati Wira Anggini; Syahidah Asma Amanina; Salwa Rainha Asyura; Romario Dion (Cell and BioPharmaceutical Institute, 2022)
Background: Klebsiella pneumoniae is known as an extended spectrum beta (β)-lactamases (ESBLs)-producing bacteria, which produces enzymes that cause resistance to β-lactam antibiotics by degrading β-lactam ring. A solution is needed to prevent the degradation of the β-lactam ring. In this in silico study, combining β-lactam antibiotics with secondary metabolites has the possibility to inhibit the active site of the β-lactamase enzyme. This study aimed to explore the potential of the essential oil of yellow bamboo (Bambusa vulgaris) leaves as inhibitors of β-lactamase. Materials and methods: This research was conducted by simulating molecular docking to determine the interaction of ligands with proteins, pharmacological tests of compounds based on the Lipinski’s rule of five, and ligand toxicity tests with pkCSM. Results: The free bond energy values (∆G) were in the range of -4.3 to -8.0 kcal/mol. The ligands with the best ∆G value were sulfur pentafluoride (-8.0 kcal/mol), squalene (-7.3 kcal/mol), 3-aminodibenzofuran (-7.1 kcal/mol), and 2- monolaurin (-5.5 kcal/mol). Secondary metabolites from the essential oil of B. vulgaris leaves fulfilled Lipinski’s rule of five, so that oral use can be carried out except for squalene and tridecane. Conclusion: Secondary metabolite compounds in the essential oil that have potential as oral drugs based on the Lipinski pharmacological test and the pkCSM toxicity test are dipivaloylmethane, β-ocimene, 2-monolaurin, and undecane. Keywords: β-lactamase, Bambusa vulgaris, essential oil, Klebsiella pneumoniae